Effects of carbonization on gangue–cemented paste backfill properties. Issue 3 (19th February 2021) - Wu, Haifeng; Liu, Yin; Li, Hao; Wang, Kai; Guo, Yalan
ABSTRACT: This study was conducted on the impact of carbonization reaction on the performance of gangue–cemented paste backfill(GCPB). Tests were conducted using a carbonization box with CO2 concentrations of 0%, 5%, and 10%. Each test was conducted for 3, 7, and 28 days. We then conducted uniaxial compressive strength(UCS)testing, as well as X-ray diffraction(XRD)and scanning electron microscopy(SEM)analyses to explore the effects of the carbonization reaction on the mechanical properties of the GCPBs under the varying carbonization concentrations. The test results showed that before 28 days, the UCS of the GCPB increased with time. The higher the CO2 concentration, the larger the contact area with the gel material;and the longer time, the slower the growth. Hydration products, such as needle-shaped ettringite(AFt)and white fibrous calcium-silicate-hydrate(C–S–H)gel, carbonize with CO2 in the air, mainly generating CaCO3, and combine with incompletely carbonized hydration products to act on the GCPB, increasing the UCS in its growth state. Moreover, we established a CO2 diffusion and mass transfer equation, indicating a negative correlation between the UCS of the GCPB and the CO2 concentration, which verified the macroscopic test results. Controlling the CO2 concentration provides the theoretical and experimental basis for the impact of the carbonization reaction on the performance of GCPBs.